ANALISIS FRAMING BERITA MAKELAR KASUS DI INSTITUSI KEPOLISIAN PADA SURAT KABAR KOMPAS DAN REPUBLIKA EDISI 19 – 23 MARET 2010 (STUDI ANALISIS FRAMING MODEL PAN DAN KOSICKI) - Kartini Rosmala Dewi Katili; Tatik Yuniarti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2011)
This study analyzed the news coverages of former Criminal Investigation Chief of the Indonesian Republic Police Headquarter, General Commissioner Susno Duadji, who stated that there were a number of police officers involved in the tax case broker event of Gayus Halomoan P. Tambunan, an official at the Tax General Directorate. The case became a controversy because a police officer dared to accuse his own institution, thus making the case come to surface and fill headlines in media. Newspapers like Kompas and Republika, for instance, covered the story simultenously on their editions dated 19 – 23 March 2010. These editions were then selected to be analyzed with framing analysis method based on the Pan and Kosicki model to find how media defined news and what messages were emphasized by media. The conclusion of this study is Kompas tend to emphasize facts related to the government, how the government followed up the case broker event at the police institution. This was indicated by the way Kompas presented the event (story telling method) in form of an interconnected news plot from the 19th to the 23rd March edition of 2010. Whereas Republika tend to focus on Susno Duadji’s acts who stated that there was a case broker in the police institution. This emphasis can be seen from the titles and figures (resources) which were descriptively presented.